Design, analysis and fabrication of mini belt sander / Azad Hazim Bahrulashikin and Ahmad Faidzal Khodori - Bahrulashikin, Azad Hazim; Khodori, Ahmad Faidzal (School of Mechanical Engineering, 2022)
Mini belt sander is a tool that is expected to change the way people make finishing for their handcrafts or some daily tasks. There are some problems that lead to this project research. Firstly, most sanding machines are relatively big, especially when handling smaller projects. Secondly, plenty of sanding machines are quite expensive and not everyone could easily afford one. This project research is intended to make a more convenient and practical sanding machine because of its compact form factor. Other than that, it is to make a sanding machine more affordable for users that are making a project for hobby or educational purposes with better quality finishing. The methodologies used for this project includes problem understanding, reviewing literature, data collecting, data analysing, and solution drawing. This project is expected to be successful and convenient for most users